The Implementation of Realistic Mathematics Learning in School (Phenomenological Study at State Junior High School 1 Manokwari) (Innovative Journal of Curriculum and Educational Technology, 2022)
This research method is a phenomenological study to describe the implementation of realistic mathematics learning in State Junior High School 1 Manokwari and to test the construction of mathematics teachers' perceptions of the meaning of realistic mathematics learning. This study uses observation, interview, and recording techniques to explore perceptions and implementations of realistic mathematics learning. The results showed that mathematics teachers at State Junior High School 1 Manokwari carried out realistic mathematics learning in a different way of perception. There is a tendency to apply the principles of realistic mathematics learning, using contextual questions that students can see, experience, or imagine to implement realistic mathematics learning in the classroom. In addition, another tendency is that teachers do not understand the concept of realistic mathematics learning, as evidenced by the lack of use of demonstration methods as motivational triggers in realizing students' mathematical ideas and concepts. Mathematics teachers need to be aware of themselves as facilitators of student learning because they build formal knowledge in a holistic and sustainable manner. This research shows that perception has a strong influence on certain decisions or actions.